Efeitos do tratamento periodontal não-cirúrgico na condição clínica periodontal e na ocorrência de parto pré-termo e/ou baixo peso ao nascimento - Alcione Moaes Soares Dutra Oliveira (2007)
In the past few years many studies have been conducted to investigate the association between maternal periodontal disease and adverse pregnancy outcomes.The present study aimed to evaluate the effects of non-surgical periodontal therapy on periodontal status in a group of pregnant women and in the occurrence of preterm birth and/or low birth weight (PTLBW) within this group. In that manner, 439 women were selected from prenatal programs of public hospitals in Belo Horizonte Brazil. Thissample included women between the 12 and 20 weeks of gestation and was divided in 5 groups according to the periodontal diagnostic and therapy. 3 groups were submitted to periodontal therapy during the gestational period: health intervention (IS), gingivitis intervention (IG), and periodontitis intervention (IP). 2 groups were submitted to periodontal therapy in the postpartum: gingivitis control (CG), and periodontitis control(CP). The present study is presented in 3 separate sections as diverse scientific papers.The first paper was a literature review regarding the relationship between maternal periodontal disease and PTLBW. This review focused issues related to study design, sample strategy and size, periodontal diagnostic criteria, pregnancy outcomes definitions, as well as major findings. The second paper involved the analysis of changes in clinical periodontal parameters among women submitted to non-surgical periodontal therapy in two different times: during gestation and postpartum. The thirdpaper included the investigation of the effects of non surgical periodontal therapy in the occurrence of preterm birth (PTB), low birth weight (LBW) and PTLBW. Findings from the present study demonstrated a worsening in periodontal status during the gestation period among women treated in postpartum. In addition, it was concluded that non-surgical periodontal treatment in the second trimester of gestation significantly improved periodontal parameters of treated women, but did not changed the risk ofPTB, LBW, and PTLBW.